1992
DOI: 10.1088/0022-3727/25/1/008
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced vaporization of a metal surface

Abstract: The laser-induced vaporization process of a metallic surface is incorporated into a simple model which describes the phase transformation and the expansion of the metal vapour against the ambient air as a function of the laser intensity and material properties. It is shown that there exists a material-dependent minimal laser intensity, where the vapour properties at the vaporization front become independent from further expansion against the ambient gas. This laser intensity is called critical intensity and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…Further investigation on the dependence of  R on T s is out of the scope of this work, it may be worthwhile to mention that the asymptotic convergence at high temperature depends more or less on geometry around the considered surface point. Aden et al [29,30] theoretically analysed metal vapour expansion dynamics in 3D geometry. It was shown that with the increase of the laser intensity and that of T s ,  R approaches ~ 0.2.…”
Section: Temperature Dependence Of Pmentioning
confidence: 99%
“…Further investigation on the dependence of  R on T s is out of the scope of this work, it may be worthwhile to mention that the asymptotic convergence at high temperature depends more or less on geometry around the considered surface point. Aden et al [29,30] theoretically analysed metal vapour expansion dynamics in 3D geometry. It was shown that with the increase of the laser intensity and that of T s ,  R approaches ~ 0.2.…”
Section: Temperature Dependence Of Pmentioning
confidence: 99%
“…Although extensive experimental and theoretical work have been done, many effects of the laser beam interaction with a metallic a͒ Electronic mail: harilal@fusion.ucsd.edu surface in the presence of ambient gas are still not satisfactorily explained. [35][36][37][38][39][40] In this article, we present a detailed experimental analysis of the laser ablation of aluminum by 2 ns gated photography and space and time resolved emission spectroscopy. Fast side-on views of the plume expansion are made by recording overall visible emission from the plasma plume, which enable us to obtain information on the interaction of the plasma with the ambient gas during earlier and later stages of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Where this compromise reasonably lies is a function of perspective. So far, the large majority of laser ablation theoretical models has been developed by physicists for physicists [1][2][3][4][5][6][7][8][9][10][11][12][13], mostly focusing on atomic scale interactions. Such atomistic models, based on either molecular dynamics or Monte Carlo approach, have been of minor appeal to analytical chemists, concerned with experiments of bhugeQ spatial scale and blongQ temporal duration.…”
Section: Introductionmentioning
confidence: 99%